Preparation and Characterization of Superabsorbents Based on Durian Seed Starch (Durio zibethinus) and Carboxymethyl Cellulose Using Citric Acid Crosslinking - Darwin Yunus Nasution; Siska Pondang (Talenta Publisher, 2024)
Superabsorbents are materials that can absorb a liquid beyond its initial volume. Natural polymer-based superabsorbents can be obtained by combining CMC and durian seed starch. The combination of these two materials was cross-linked using varying amounts of citric acid: 0.0 grams, 0.2 grams, 0.4 grams, and 0.6 grams. The resulting superabsorbent has a cross-linking degree of about 41%, shows the presence of OH and CH groups, has a rough and dense surface, and a maximum water absorption capacity of 4130% with a water absorption rate of 41.3 g/g. Durian seed starch has potential as a superabsorbent material.